Sociodemographic correlates of older adult acceptance of the COVID-19 vaccine - Arlene Supremo; Sillmark Bacason; Alexander Rex Sañosa (Universitas Airlangga, 2022)
Introduction: An increase of the COVID-19 global statistics in late 2019 prompted the swift manufacturing of vaccines to protect people, especially older adults, from the debilitating effects of the disease. This study aimed to determine the socio-demographic correlates of older adults and their relationship with COVID-19 vaccine acceptance. Methods: This correlational study invited the entire population of older adults to answer the survey. In total, 89 elderly individuals participated in face-to-face interviews because of the old age limitations. The tool used consisted of two parts. The first part determined the socio-demographic correlates. The second part assessed the level of acceptance of the COVID-19 vaccine. Rank Biserial and Spearman Rho were used to measure the correlations between the sociodemographic variables and COVID-19 vaccine acceptance. Results: The respondents were predominantly female (n = 45; 50.56%), with an elementary level of education (n = 48; 53.93%), below PHP 10,000.00 for monthly family income (n=77; 86.52%), unemployed (n=79; 88.76%), and Roman Catholic (n = 87; 97.75%). Generally, older adults will not accept the COVID-19 vaccine, specifically if it has less than a 50% effectiveness (n = 51; 57.30%) and if they have existing medical conditions (n = 51; 57.30%). Finally, the findings suggest that employment status has a significant negative relationship with the acceptance of the COVID-19 vaccine (r = -0.357, p = 0.0001). Conclusions: 47.19% to 57.30% of older adults will not accept the COVID-19 vaccine. National and local governmentunits need to intensify their vaccination campaigns to persuade the public to engage with the free COVID-19 vaccines.